A systems approach for collaborative decision support in water resources planning. (1st January 2000) - Bender, Michael J.; Simonovic, Slobodan P.
This paper presents a systems approach for collaborative group planning of water development projects. Two dynamic modelling paradigms were considered for development of a collaborative planning support system (CPSS). One paradigm is based on negative feedback, which forces system transformation towards an external goal. The selected paradigm is based on the concept of positive feedback. Positive feedback behaves in a similar manner to many natural growth processes in which the system feedback instigates growth away from an external goal or reference point. The positive feedback approach initiates changes to a proposal away from the initial reference point of conflict or disjoint value systems. This approach forms the basis of a framework for decision support system development. The decision support system is designed for interaction and participation of a group of stakeholders with a project proponent for the purpose of examining options for hydropower generating station configuration. Planning within the group setting assumes an iterative, flexible, modelling posture. Stakeholders are able interactively to adjust the configuration details to improve understanding of system behaviour and consequences of choices. Experimental alternatives are compared in terms of decision robustness relative to apparent value systems or preference structures. Overall, the positive feedback mechanisms of iteration and experimentation allow alternatives to be generated, assessed, and improved.